Bad Smells and Broken DNA: A Tale of Sulfur-Nucleic Acid Cooperation - Rodney E. Shackelford; Yan Li; Ghali E. Ghali; Christopher G. Kevil (MDPI AG, 2021)
Hydrogen sulfide (H2S) is a gasotransmitter that exerts numerous physiologic and pathophysiologic effects. Recently, a role for H2S in DNA repair has been identified, where H2S modulates cell cycle checkpoint responses, the DNA damage response (DDR), and mitochondrial and nuclear genomic stability. In addition, several DNA repair proteins modulate cellular H2S concentrations and cellular sulfur metabolism and, in turn, are regulated by cellular H2S concentrations. Many DDR proteins are now pharmacologically inhibited in targeted cancer therapies. As H2S and the enzymes that synthesize it are increased in many human malignancies, it is likely that H2S synthesis inhibition by these therapies is an underappreciated aspect of these cancer treatments. Moreover, both H2S and DDR protein activities in cancer and cardiovascular diseases are becoming increasingly apparent, implicating a DDR-H2S signaling axis in these pathophysiologic processes. Taken together, H2S and DNA repair likely play a central and presently poorly understood role in both normal cellular function and a wide array of human pathophysiologic processes. Here, we review the role of H2S in DNA repair.